Humanized delivery: benefits and barriers to its implementation - Silva, Esther Lima da (2021)
The concept of humanized childbirth goes beyond the idea of comfort and the minimization of pain at the time of delivery, but covers a set of measures from prenatal to postpartum, which aim to provide women with a high degree of satisfaction, autonomy, and safety. This study is a literature review, which aims to understand the importance of the humanization of childbirth for the mother-baby binomial and to identify the barriers faced by health professionals for its implementation. To carry out the research, the databases BVSalud and SCIELO were used, using the controlled descriptor "Humanized Childbirth", free search with the terms: "Father and humanized childbirth" and "Childbirth and black women" in addition to consultations on official websites related to health. For inclusion of articles, it was filtered by the years from 2016 to 2021 with Portuguese, English or Spanish language and full texts consistent with the subject of the research to be performed. The results of the studies pointed out that the humanization process contributes to a better experience of childbirth and puerperium for the woman, consequently benefiting the baby and the entire family network. However, for this process to be successful, the technical and scientific knowledge of the health professionals in charge is important, as well as the support for its implementation. Such factors seem to interfere with the humanization process.